GPIbα is the driving force of hepatic thrombopoietin generation - Danielle Karakas; Miao Xu; Heyu Ni (Research and Practice in Thrombosis and Haemostasis, 2021)
Abstract Thrombopoietin (TPO), a glycoprotein hormone produced predominantly in the liver, plays important roles in the hematopoietic stem cell (HSC) niche, and is essential for megakaryopoiesis and platelet generation. Long‐standing understanding proposes that TPO is constitutively produced by hepatocytes, and levels are fine‐tuned through platelet and megakaryocyte internalization/degradation via the c‐Mpl receptor. However, in immune thrombocytopenia (ITP) and several other diseases, TPO levels are inconsistent with this theory. Recent studies showed that platelets, besides their TPO clearance, can induce TPO production in the liver. Our group also accidentally discovered that platelet glycoprotein (GP) Ibα is required for platelet‐mediated TPO generation, which is underscored in both GPIbα−/− mice and patients with Bernard‐Soulier syndrome. This review will introduce platelet versatilities and several new findings in hemostasis and platelet consumption but focus on its roles in TPO regulation. The implications of these new discoveries in hematopoiesis and the HSC niche, particularly in ITP, will be discussed.